Contextualising workplace mental health in post-pandemic South Africa: A systematic review - Nelesh Dhanpat; Boitumelo Makhubele; Roslyn De Braine (SA Journal of Industrial Psychology, 2025)
Orientation: Post-pandemic, mental health issues remain prevalent, highlighting the need for promoting workplace mental health. This study emphasises the importance of contextualising these issues to understand the workplace mental health landscape in post-pandemic South Africa.